Penerapan Regresi Cox untuk Menganalisis Variabel yang Berpengaruh Terhadap Durasi Studi Mahasiswa - Widyastuti, Rhoudhotul; Wulandari, Dewi; Prasetyowati, Dina (STATMAT : JURNAL STATISTIKA DAN MATEMATIKA, 2025)
This research aims to obtain the Cox regression equation in managing student study duration data and to determine variables or factors that significantly influence student study duration. We used data from 2017 FPMIPATI (Fakultas Pendidikan Matematika, Ilmu Pengetahuan Alam dan Teknologi Informasi) UPGRIS (Universitas PGI Semarang) Mathematics Education study program students which consisted of four predictor variables including gender, cumulative achievement index, parents' educational background, and organizational participation. From the results of the survival analysis, it was found that the factor that had a significant influence on the duration of student studies was the cumulative achievement index.